Variable features of 18F-fluorodeoxyglucose positron emission tomography–computed tomography scan in anorectal malignant melanoma: Case reports and review articles - Digish Shah (World Journal of Nuclear Medicine)
Anorectal malignant melanoma (ARM) is a rare variant of malignant melanoma and even more rare among all anorectal cancers. 18F-fluorodeoxyglucose (FDG) positron emission tomography–computed tomography (CT) scan is valuable in staging, restaging, treatment response evaluation, and long-term follow-up of malignant melanoma. Here, reporting two cases of anorectal melanoma with a variety of FDG uptake pattern and CT-based features and reviewed a few articles to evaluate the pattern of FDG uptake.